Informator . no. 9, 1981 - "Solidarność" Biuro Informacyjne Zarządu Regionu Środkowo-Wschodniego, [ed. M. Sobieraj et al.] (NSZZ "Solidarność" Region Środkowo-Wschodni, 1981)
Creation and circulation: After introduction of the Martial Law publication suspended. Republished underground in January 1982